Triple burden of malnutrition among Malaysian children aged 6 months to 12 years: current findings from SEANUTS II Malaysia - Bee Koon Poh; Jyh Eiin Wong; Shoo Thien Lee; Jasmine Siew Min Chia; Giin Shang Yeo; Razinah Sharif; Nik Shanita Safii; Nor Aini Jamil; Caryn Mei Hsien Chan; Nor MF Farah; Mohd Jamil Sameeha; Denise Koh; et al. (Cambridge University Press, 2024)
Abstract Objective: This paper aims to report South East Asian Nutrition Surveys (SEANUTS) II Malaysia data on nutritional status, dietary intake and nutritional biomarkers of children aged 6 months to 12 years. Design: Cross-sectional survey conducted in 2019-2020. Setting: Multistage cluster sampling conducted in Central, Northern, Southern and East Coast regions of Peninsular Malaysia. Participants: 2989 children aged 0·5-12·9 years. Results: Prevalences of stunting, thinness, overweight and obesity among children aged 0·5-12·9 years were 8·9 %, 6·7 %, 9·2 % and 8·8 %, respectively. Among children below 5 years old, 11·4 % were underweight, 13·8 % had stunting and 6·2 % had wasting. Data on nutritional biomarkers showed that a small proportion of children aged 4-12 years had Fe (2·9 %) and vitamin A deficiencies (3·1 %). Prevalence of anaemia was distinctly different between children below 4 years old (40·3 %) and those aged 4 years and above (3·0 %). One-fourth of children (25·1 %) had vitamin D insufficiency, which was twice as prevalent in girls (35·2 % v. boys: 15·6 %). The majority of children did not meet the recommended dietary intake for Ca (79·4 %) and vitamin D (94·8 %). Conclusions: Data from SEANUTS II Malaysia confirmed that triple burden of malnutrition coexist among children in Peninsular Malaysia, with higher prevalence of overnutrition than undernutrition. Anaemia is highly prevalent among children below 4 years old, while vitamin D insufficiency is more prevalent among girls. Low intakes of dietary Ca and vitamin D are also of concern. These findings provide policymakers with useful and evidence-based data to formulate strategies that address the nutritional issues of Malaysian children.